Trauma and resistance in Niger's emergency transit mechanism: A life narrative study - Chiara Fiscone; Lorenzo Montali; Camilla Pagani; Marzia Vigliaroni; Guido Veronese (Elsevier, 2024)
This qualitative exploratory research delves into the intricate life narratives of forcibly displaced individuals residing within the Emergency Transit Mechanism in Niger, employing a methodology grounded in life narrative analysis. The primary objective is to gain a comprehensive understanding of the potential stressors and traumatic experiences encountered by these individuals, encompassing both psychological and physiological dimensions, while also examining the dynamics of resilience and elements contributing to their overall well-being. The findings, derived through thematic content analysis, underscore the cumulative nature of traumatic events experienced by migrants throughout their lifetimes and across various stages of the migration continuum. The study, in alignment with extant scholarly literature, identifies thematic categories such as "A scenario of conflict and mourning, '' everyday experience of violence and discrimination," "health at risk", and '' Seeking security." Refugees recount enduring multiple traumas, including familial bereavements and losses resulting from conflicts and militarized violence. Furthermore, the analysis elucidates a profound interplay between traumatic occurrences, subjective well-being, and resilience among the studied population. Despite confronting adverse living circumstances, refugees demonstrate indicators of subjective well-being, hinting at the potential for resilience and recovery. This challenges conventional diagnostic frameworks such as Post-Traumatic Stress Disorder (PTSD) and underscores the necessity for a nuanced understanding of trauma's multifaceted impacts. Nevertheless, the study underscores the urgent need for a more robust and contextually attuned mental health support infrastructure, advocating for a deeper exploration of the socio-political determinants underpinning forced migration. By comprehending the root causes of displacement through a socio-political lens, policymakers and practitioners can devise comprehensive strategies and interventions aimed at both prevention and mitigation of factors precipitating forced migration. This approach seeks to foster a global landscape wherein compassionate and well-informed interventions proactively address the underlying drivers of displacement.